2005
DOI: 10.1111/j.1471-4159.2005.03187.x
|View full text |Cite
|
Sign up to set email alerts
|

mTOR/p70S6k signalling alteration by Aβ exposure as well as in APP‐PS1 transgenic models and in patients with Alzheimer's disease

Abstract: In Alzheimer's disease, neuropathological hallmarks include the accumulation of b-amyloid peptides (Ab) in senile plaques, phosphorylated tau in neurofibrillary tangles and neuronal death. Ab is the major aetiological agent according to the amyloid cascade hypothesis. Translational control includes phosphorylation of the kinases mammalian target of rapamycin (mTOR) and p70S6k which modulate cell growth, proliferation and autophagy. It is mainly part of an anti-apoptotic cellular signalling. In this study, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
170
3
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 197 publications
(192 citation statements)
references
References 49 publications
14
170
3
1
Order By: Relevance
“…It is clear, however, that the role of mTOR in AD is very complex; although it is established that in human AD brains mTOR signaling is increased, especially in neurons predicted to develop Tau pathology, diverging results have been published on the effects of A␤ on mTOR signaling in cell lines. For example, A␤ application to differentiated N2A neuroblastoma cells following 10% serum deprivation significantly decreases the levels of phosphorylated p70S6K (64), whereas differentiated human SH-SY5Y cells exposed to A␤42 show an increase in phosphorylation levels of p70S6K (65). Our data showing an increase in p70S6K phosphorylation in 7PA2 cells are consistent with the latter but appear to be conflicting with the effects of A␤ on N2A cells.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…It is clear, however, that the role of mTOR in AD is very complex; although it is established that in human AD brains mTOR signaling is increased, especially in neurons predicted to develop Tau pathology, diverging results have been published on the effects of A␤ on mTOR signaling in cell lines. For example, A␤ application to differentiated N2A neuroblastoma cells following 10% serum deprivation significantly decreases the levels of phosphorylated p70S6K (64), whereas differentiated human SH-SY5Y cells exposed to A␤42 show an increase in phosphorylation levels of p70S6K (65). Our data showing an increase in p70S6K phosphorylation in 7PA2 cells are consistent with the latter but appear to be conflicting with the effects of A␤ on N2A cells.…”
Section: Discussionsupporting
confidence: 63%
“…The role of autophagy in AD is not well understood and contradicting reports have been published. For example, it has been reported that autophagic vacuoles may be a source of A␤ production and that autophagic vacuoles accumulate in AD brains and in APP/PS1 transgenic mice, thus suggesting that an increase in autophagy may lead to a further accumulation of A␤ (64,66,67). In contrast, other reports show that autophagy protects neurons from A␤ toxicity (59,60,68,69).…”
Section: Discussionmentioning
confidence: 66%
“…We found that hippocampal p70S6K level suppressed following Aβ injection that was prevented by GA pretreatment, concurrent with improvement in PA memory. In this manner, both in vitro and in vivo administration of Aβ by Lafay-Chebassier et al (2005) resulted in significant decrease in p70S6K signaling. Although in another independent study of AD patients there was an aberrant activation of p70S6K, it was attributed to neurofibrillary pathology and tau phosphorylation, not Aβ .…”
Section: Discussionmentioning
confidence: 96%
“…( Lafay-Chebassier et al, 2005;Paccalin et al, 2006a,b). Based on these data, we studied the role of the mTOR pathway as a specific translation regulator in the cortex after acquiring novel sensory information.…”
Section: Discussionmentioning
confidence: 99%